Spectrum of mitochondrial genomic variation and associated clinical presentation of prostate cancer in South African men. Issue 4 (10th December 2015) - McCrow, John P.; Petersen, Desiree C.; Louw, Melanie; Chan, Eva K. F.; Harmeyer, Katherine; Vecchiarelli, Stefano; Lyons, Ruth J.; Bornman, M. S. Riana; Hayes, Vanessa M.
Abstract : BACKGROUND: Prostate cancer incidence and mortality rates are significantly increased in African–American men, but limited studies have been performed within Sub–Saharan African populations. As mitochondria control energy metabolism and apoptosis we speculate that somatic mutations within mitochondrial genomes are candidate drivers of aggressive prostate carcinogenesis. METHODS: We used matched blood and prostate tissue samples from 87 South African men (77 with African ancestry) to perform deep sequencing of complete mitochondrial genomes. Clinical presentation was biased toward aggressive disease (Gleason score >7, 64%), and compared with men without prostate cancer either with or without benign prostatic hyperplasia. RESULTS: We identified 144 somatic mtDNA single nucleotide variants (SNVs), of which 80 were observed in 39 men presenting with aggressive disease. Both the number and frequency of somatic mtDNA SNVs were associated with higher pathological stage. CONCLUSIONS: Besides doubling the total number of somatic PCa‐associated mitochondrial genome mutations identified to date, we associate mutational load with aggressive prostate cancer status in men of African ancestry. Prostate 76:349–358, 2016 . © 2015 The Authors. The Prostate published by Wiley Periodicals, Inc.